Advances in Cryptology — CRYPTO’ 93: 13th Annual International Cryptology Conference Santa Barbara, California, USA August 22–26, 1993 Proceedings - Stinson, Douglas R. (Lecture notes in computer science, 1994)
This volume contains the papers presented at the CRYPTO '93 conference. The conference was sponsored by the International Association for Cryptologic Research (IACR) and Bell-Northern Research (a subsidiary of Northern Telecom) and held in cooperation with the IEEE Computer Society. These proceedings contain revised versions of the 38 contributed talks, as well as two talks from the rump session. The papers are grouped into parts on: cryptosystems, stream ciphers and cryptographic functions, proof systems and zero-knowledge, secret sharing, number theory and algorithms, differential cryptanalysis, complexity theory, applications, authentication codes, hash functions, cryptanalysis, and key distribution
Literaturangaben
Keywords: Konferenzschrift -- 1993 -- Santa Barbara, Calif.; Konferenzschrift; Kryptologie